Perlawanan Umat Islam Terhadap Penjajahan di Indonesia - Saribunga Saribunga; Hasaruddin Hasaruddin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research discusses the central role of the Muslim community in resisting colonial powers in the Indonesian archipelago, focusing on colonization by the Dutch, Spanish, Portuguese, French, British, and Japanese. Islamic teachings, particularly the concepts of jihad, love for the homeland, and resistance to oppression, played a pivotal role in igniting the spirit of resistance. Islamic Sultanates such as Aceh, Demak, and Mataram actively engaged in the struggle, along with the leadership of scholars and the general population. With low literacy rates, the positive transformations during British colonization were limited in their full utilization by the local communities. Although Japan initially attempted to garner support by claiming liberation, it eventually proved to be a harsh colonizer with forced labor programs. This research employs the library research method to explore the dynamics of Muslim resistance against colonizers by utilizing literary sources.